Stromal matrix metalloproteinase 2 regulates collagen expression and promotes the outgrowth of experimental metastases. Issue 5 (5th January 2015) - Bates, Andreia L; Pickup, Michael W; Hallett, Miranda A; Dozier, E Ashley; Thomas, Stacy; Fingleton, Barbara
Abstract: Breast cancer survival rates decrease from 99% for patients with local disease to 25% for those with distant metastases. Matrix metalloproteinases (MMPs), including MMP2, are associated with metastatic progression. We found that loss of host MMP2 reduces the proliferation of experimental metastases in the lungs and identified fibroblasts in tumour‐bearing lungs as the major source of MMP2. In vitro, spheroidal mammary tumour growth was increased by co‐culture with control fibroblasts isolated from tumour‐bearing lungs, but not when fibroblasts with stable Mmp2 knockdown were used. This result prompted us to assess whether MMP2 was responsible for a tumour‐proliferative, activated fibroblast phenotype. To test this, we evaluated: (a) fibroblasts from wild‐type tumour‐bearing lungs, with or without shRNA‐mediated MMP2 knockdown; and (b) normal, quiescent fibroblasts isolated from either WT or Mmp2 –/– mice. Quantitative PCR revealed that Mmp2 knockdown attenuated expression of two markers of activation ( α ‐smooth muscle actin and vimentin), but there was minimal expression in quiescent WT or Mmp2 –/– fibroblasts, as expected. Placing quiescent fibroblasts under activating conditions led to increases in activation‐associated transcripts in WT but not Mmp2 –/– fibroblasts. Additionally, Mmp2 knockdown fibroblasts showed significantly decreased expression of the matrix transcripts collagen I, collagen IV and fibronectin. Addition of active TGF β was sufficient to rescue the MMP2‐dependent collagen I and IV expression, while MMP2‐induced collagen expression was blocked by the addition of TGF β 1‐neutralizing antibody. Gene expression data in stromal cells of human breast cancers reveal that MMP2 expression is also positively correlated with activation and matrix transcripts. Thus, we present a model whereby MMP2 production in tumour fibroblasts is important for TGF β 1 activity and subsequent activation of fibroblasts to a matrix‐producing, proliferation‐supportive phenotype. Overall, our results reveal a previously undefined role for MMP2 in metastatic outgrowth mediated by fibroblasts, and extend the mechanisms by which MMPs contribute to tumour progression. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.